Neonatal candida infections in an intensive care unit: A three year experience - (:unkn) unknown (My University, 2000)
Objective: Although technological advances in neonatal care increase survival rate in premature babies, they also contribute to the increasing incidence of systemic candida infections in this population. Therefore, we aimed to evaluate cases with systemic candida infections and discuss the results. Methods: Eighteen neonates with disseminated candidiasis were evaluated according to their risk factors, culture results and antifungal susceptibilities. Results: Fourteen out of eighteen were preterms and eleven of them weighed less than 1500 grams. The Candida species isolated from blood, urine or cerebrospinal fluid were Candida albicans in nine (50%), Candida parapsilosis in six (33%), Candida spp. in two (11%) cases and Candida pseudotropicalis in one (6%) case. Antifungal susceptibility of the isolates to amphotericin B (AMB) and fluconazole (FCZ) was determined using the macrodilution method. Four of our patients received AMB while FCZ was started in fourteen cases but only ten of them showed good clinical and mycological response. In four patients the treatment was continued with AMB because of poor clinical response although only one of them had a high minimal inhibitory concentration level to FCZ. All of our patients were treated successfully without any complication. Conclusion: Early recognition and treatment of infants with systemic candida infection will reduce morbidity and mortality. Identifying the Candida species and determining their susceptibility may be useful in planning the treatment of neonatal candidemia.
Keywords: Newborn; Systemic candidiasis